Impact of prophylactic biliary stenting on stone recurrence and post-endoscopic retrograde cholangiopancreatography complications in patients awaiting cholecystectomy: a randomized controlled trial - Mishra, Prakash Chandra; Kumar, Ujjwal; Dubey, Rohit (International Journal of Research in Medical Sciences, 2025)
Background: Recurrence of common bile duct (CBD) stones and post-endoscopic complications remain clinical concerns in patients awaiting elective cholecystectomy. The use of prophylactic biliary stents after complete stone clearance is debated, with conflicting evidence regarding their efficacy and safety. This study aimed to evaluate whether biliary stent placement after duct clearance reduces recurrence or contributes to procedural complications. Methods: A prospective, randomized controlled trial was conducted over one year at a tertiary care center in Bihar, India. Patients with confirmed choledocholithiasis who achieved complete CBD clearance through endoscopic retrograde cholangiopancreatography (ERCP) were randomized into two arms: Group A received prophylactic biliary stents (n=42), and group B did not receive stents (n=38). Patients were monitored for three months through clinical reviews and imaging (endoscopic ultrasound or MRCP). The primary outcome measured was recurrence of CBD stones. Secondary outcomes included incidence of post-procedure complications and need for repeat ERCP. Results: Of the 80 participants, 42 were allocated to the stent arm and 38 to the no-stent arm, all of whom completed the study. Recurrent common bile duct stones developed in 8 patients (19.0%) in the stent group versus 3 patients (7.9%) in the non-stent group. The stent cohort demonstrated a higher overall complication rate (11.9%), with events such as post-ERCP pancreatitis and acute cholecystitis, whereas no complications were recorded in the non-stent cohort. Although repeat ERCP was required more often among those who received stents, the difference was not statistically significant. Conclusions: The findings suggest that prophylactic biliary stenting after successful CBD clearance does not reduce recurrence risk and may increase the likelihood of complications. These results call for careful reconsideration of routine stent use in patients awaiting cholecystectomy.